Of criteria and perceptions a study of web resource evaluation by the undergraduate students of the University of the Philippines Los Baños - Cervantes, Nicolo Lorenzo T.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study focused on the perception of the undergraduate students of the University of the Philippines Los Baños on how they evaluate and perceive the quality of information they get from Web resources. A total of 340 students of English 2, an English composition class were surveyed. The subject was chosen as it would require students to produce a research paper. A questionnaire was used for the survey, which was extensively modified from Judd, Farrow and Tims's 2006 website evaluation form. It asked among others, their general opinion of the Internet as a research tool, their usage of different criteria for determining quality of information, and their perception of the information quality of different kinds of websites.
Data gathered from the questionnaire indicated that: (a) students have a generally favorable opinion of the Internet; (b) of the criteria tested, they utilized trustworthiness the most and expertise the least; (c) among the sites included in the study, news and academic websites have the most favourable perception; (d) personal websites, discussion boards, and wiki sites had the least favourable perception among the sites included in the study, and; (e) majority of the respondents said that they would like to be allowed to use Web resources more due to its accessibility.
Recommendations included a follow-up study in response to a new large class policy implemented in subsequent semesters, further collaboration between librarians and teachers, and the introduction of an information literacy course.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- College students; Computer network resources -- Philippines -- Laguna (Los Baños) -- Evaluation